MODEL COOPERATIVE LEARNING TIPE JIGSAW TERHADAP PEMBELAJARAN KEMAMPUAN HANDSPRING SENAM LANTAI - Samsul Aspin; Mimi Haetami; Eka supriatna (Universitas Tanjungpura, 2019)
AbstractThe problem of this research was to know whether there was an influence of the cooperative learning model of jigsaw on learning gymnastic handspring skills on students at SMAN 1 Teluk Batang Kayong Utara. This study aimed to determine the effect of the cooperative learning model of jigsaw on learning result of gymnastic handspring on students at sman 1 teluk batang kayong utara.The method that had been applied in this research was an experimental method. Moreover, the design of this research was pre-experimental design and for the research plan used one group pretest-posttes design. The research population in this research was 20 students in grade XI (IPS 2) SMAN 1 Teluk Batang Kayong Utara in academic year 2019/2020. The sample of this research was 20 students with Handspring test for the technique of data collection. Data analysis was analyzed descriptively using -t test ( effect test )From the result of the research, it can be conclude that there is significant effect of cooperative learning model type of jigsaw on learning gymnastic handspring skills to students at SMAN 1 Teluk Batang Kayong Utara. The result of analysis -t test showed that the calculated value (9,211) and table (2,093) or (9,211> 2,093). The percentage of the impact that is obtained by using cooperative learning model towards gymnastic handspring skills on students at SMAN 1 Teluk Batang Kayong Utara was 39.62%Keywords : model cooperative learning , jigsaw gymnastic handspring.